Association between infant feeding and early childhood caries: a review of literature - Massón Palacios, María José (2019)
Objectives: the present review aims to verify in the literature currently available, the influence of the practice of breastfeeding on the risk of early age caries. Materials and methods: A bibliographic search was conducted in the Pubmed and Scielo databases, between 2013 and 2018, category “free full text”, the inclusion criteria were case study articles, clinical trials, meta-analyzes, systematic reviews and literature reviews, using as terms of search ((caries OR dental caries OR dental decay OR decay OR decayed teeth OR tooth decay) AND (breastfed OR breast fed OR breastfeeding)), 62 articles were obtained, after reading, analysis and application of the exclusion criteria, 42 articles were discarded, leaving 10 articles that were considered the most relevant for the review proposed on the date of its realization. Results: The articles reviewed determined the close asociation between breastfeeding practices and the presence of caries at an early age, especially when this is done with a high daily frequency, a prolonged duration, during night periods and when oral hygiene procedures are not they are executed. Conclusions: the benefits of breastfeeding are evident, the reviewed literature reveals the importance of this practice, accompanied by complementary oral hygiene measures.